PENDIDIKAN ANAK DALAM SERAT WULANG SUNU KARYA SUNAN PAKUBUWONO IV: Sebuah Analisis Isi - Iflahathul Chasanah; Abdul Munip; Mukhibat Mukhibat (Cendekia: Kependidikan dan Kemasyarakatan, 2018)
The paper aims to describe the child education in Serat Wulang Sunu written by Sunan Pakubuwono IV. The writer focuses on content, purpose, subject matter, a method of education and also the relevance of educational values of Serat Wulang Sunu currently. The result is Serat Wulang Sunu teach the children behavioral ethics to parent and the other. The education purpose is creating the child dutiful to the parents as a child ideal profile. Subject matter thought by Serat Wulang Sunu involved politeness, respect to parents, command, and prohibition with parents. The method that used in Serat Wulang Sunu thought through the advice, prohibition, threat, and an appointment. The thought and education values in Serat Wulang Sunu still relevance when used in the education system today. Serat Wulang Sunu has universal thought and values that must be preserved for human life.هذه الكتابة لتصريح تربية الطّللّاب في " Serat Wulang Sunu" لسنن فاكوبووانا. اما تركين هذا البحث هو التضمين, والهدف, والمادة, ومنهج الدراسة, ومنهج التربية في "سورة وولاع سونو" ثم صلح القيم التربوية في " Serat Wulang Sunu " مع تعليم الحالي. هذا النوع من البحوث هو دراسة الأدب. تم تحليل البيانات باستخدام تحليل المحتوى. نتائج هذه الدراسة هي محتويات التعاليم  في " Serat Wulang Sunu " هو زراعة القيم التعبدية للأطفال ليكون لديهم موقف طاعة الوالدين. الغرض من التعليم هو تكوين أطفال مطيعين لأولياء الأمور كالملف المثالي للطفل. المادة التي يتم تدريسها في" Serat Wulang Sunu " هو تعليم القيم العالمية. الطريقة المستخدمة في التعليم "سورة وولاع سونو" هو من خلال الطريقة الشفهية. التعليم و القيم التعليمية الواردة في " Serat Wulang Sunu " ذات الصلة إذا استخدمت في التعليم اليوم. " Serat Wulang Sunu " لديه التعاليم والقيم العالمية التي يتم الحفاظ عليها في حياة الإنسان.